Mechanical and Microstructural Characterization of Metals and Alloys - Silvia Barella; Dario Ripamonti (Crystals, 2020)
In order to design a fully functional manufactured component the designer needs a deep understanding of the materials behavior, which includes not only its in-service performance but also the effect of the processing routine [...]